The Learning Activity of Dance Art in the Development of Motor Skills in Students of SDN 11 Rejang Lebong - Dewi, Jauhari Kumara; Oktira, Yona Syaida (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
One effective way to develop motor skills in children is through fun and creative physical activities, such as dance. Learning is an interactive activity between educators and students carried out in schools, the most important of which is a systematic plan to achieve learning goals. In this context, it is important to further explore how dance learning activities can be used as an effective means to help students' motor development. With a deeper understanding of the contribution of dance to motor development, it is hoped that more schools will implement this activity in their curriculum, so that it can improve the quality of physical and arts education in Indonesia. This study uses a descriptive qualitative research type. Where this study aims to describe or describe art activities, which are generally in the form of dance works such as basic dance movements. Dance not only functions as a means of artistic expression, but also has a significant positive impact on children's motor development. By integrating dance into children's education, we can support their physical development holistically, both in terms of gross motor skills and fine motor skills.